2004
DOI: 10.1103/physreve.70.067302
|View full text |Cite
|
Sign up to set email alerts
|

Observation of strongly non-Gaussian statistics for random sea surface gravity waves in wave flume experiments

Abstract: We study random surface gravity wave fields and address the formation of large-amplitude waves in a laboratory environment. Experiments are performed in one of the largest wave tank facilities in the world. We present experimental evidence that the tail of the probability density function for wave height strongly depends on the Benjamin-Feir index (BFI)-i.e., the ratio between wave steepness and spectral bandwidth. While for a small BFI the probability density functions obtained experimentally are consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
150
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 16 publications
11
150
0
1
Order By: Relevance
“…Recent experiments in water waves [26], [9] and in fibre optics [31], [21], [22], [16] (see also review articles [5], [10]) have convincingly demonstrated that rogue waves are a generic physical phenomenon deserving a comprehensive investigation [27], [5]. It has also been understood that rogue waves play important role in the characterization of the nonlinear stage of modulational instability [41], [17] and particularly, in the development of integrable turbulence [40], [1], [37], [33].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments in water waves [26], [9] and in fibre optics [31], [21], [22], [16] (see also review articles [5], [10]) have convincingly demonstrated that rogue waves are a generic physical phenomenon deserving a comprehensive investigation [27], [5]. It has also been understood that rogue waves play important role in the characterization of the nonlinear stage of modulational instability [41], [17] and particularly, in the development of integrable turbulence [40], [1], [37], [33].…”
Section: Introductionmentioning
confidence: 99%
“…Also in this case results are available from both laboratory experiments [25,29] and numerical simulations [15,33,12,28,32,36]. A central finding of such studies consists of the intensification of extreme wave activity for high values of the Benjamin-Feir index (see § 2.1), i.e., when the power spectrum of the surface elevation is sharply peaked around the fundamental wavenumber.…”
Section: Introductionmentioning
confidence: 99%
“…If extreme waves are to be considered a consequence of breathing modes embedded in a random background [25], then the increased probability of extreme waves for narrowbanded spectra should reflect into a stronger presence of organized structures within the wave field. This is the main point under investigation in this paper, which is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the observational data [Dankert et al, 2003], the stochastic Rayleigh model greatly underestimates the probability of freak waves. Recent advances in technology have allowed multiple wave tank experiments and field observations to be conducted, confirming the need for a more realistic theory to explain the results [Forristall, 2000;Onorato et al, 2004].…”
Section: Introductionmentioning
confidence: 96%
“…[3] The scientific community has studied the topic experimentally (in water tanks) [Onorato et al, 2004[Onorato et al, , 2006, observationally (with satellite imaging, for example) [Dankert et al, 2003;Schulz-Stellenfleth and Lehner, 2004], and theoretically [Kharif and Pelinovsky, 2003]. A review of recent progress in freak wave forecasting can be found in an article by Dysthe et al [2008].…”
Section: Introductionmentioning
confidence: 99%